Viscosity and Liquidity Index Relation for Elucidating Mudflow Behavior - Budijanto Widjaja; Shannon Hsien-Heng Lee (Bandar Lampung University (UBL), 2013)
The mechanism of mudflow, which is a type of mass movement, is different from that of landslide. A landslide has a discrete failure surface, whereas a mudflow has flow characteristics. Hence, the conventional approach of explaining the characteristics of landslide is not applicable in mudflow. The adaptation of rheological models, such as the Bingham and Herschel–Bulkley models, is required to explain the characteristics of mudflow. Qualitative classifications of mudflow based on water content are also available. The mass movement of mudflow is initiated when the water content of the mudflow is equal to or higher than its liquid limit. Thus, the mass movement of mudflow occurs when the mud is in a viscous liquid state. However, up to now, a detailed explanation on how mudflow is initiated by using a rheological approach is nonexistent. In this study, a flow box test is developed to determine the rheological parameters of mud, including yield stress and viscosity. This test is established to overcome the lack of conventional viscometers, which can only measure the rheological properties of mud in a viscous liquid state. The flow box test utilized the Bingham model and a couple of trap door mechanisms. Results are then interpreted using a method similar to the Herschel–Bulkley model. The flow box test provides reliable results for both plastic and viscous liquid states. Results show that the mudflow characteristics can be explained based on the changes in viscosity. Sudden changes in viscosity occur when the mud reaches its liquid limit, implying that mudflow is possibly triggered when the soil water content of the mud is equal to its liquid limit. The results of this study provide a detailed explanation of mudflow initiation.